Conversão de glicerol em ácido lático utilizando catalisadores heterogêneos de paládio e platina suportados em carbono ativado - Arcanjo, Maria Rosiene Antunes (2017)
For every 9 tons of biodiesel produced, about 1 ton of crude glycerol is formed. By 2020 it is estimated that world production of glycerol will reach 3 million tons, while its demand will not exceed 500 thousand tons, so alternatives are needed for the use of residual glycerol in order to ensure both economic viability of the biodiesel production and the impact generated in the environment with this surplus volume. Due to its high functionalization, glycerol can be transformed into several value-added products, such as lactic acid. In this context, the present thesis investigated the production of lactic acid from glycerol using Pd (palladium) and Pt (platinum) supported on activated carbon as catalysts. The Pt and Pd catalysts supported on AC were synthesized and characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission (TEM), Textural Analysis Techniques, Spectroscopy X-ray Photoelectron (XPS), Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) and Boehm's method. It was studied the parameters that influence the performance of the catalysts as: metal loading (%), amount of catalyst (g), molar ratio NaOH:Glycerol, support pretreatment (AC), temperature and time reaction. The operating conditions which maximized the lactic acid content and its yield were: temperature (230 °C), reaction time (180 minutes), catalyst concentration (5% Pt and 10% Pd) and NaOH:Glycerol (1.1) for both catalysts. The catalysts studied were considered stable for 5 cycles of reuse, obtaining conversions ranging from 85.9 to 99%, and 88.3 to 99% for 5% Pt and 10% Pd for AC, respectively. Finally, catalytic tests with the own glycerine coming from the biodiesel production for both catalysts studied were obtained, obtaining smaller results in relation to the catalytic tests carried out with pure glycerol, however considered satisfactory considering that the crude glycerin can still be purified to removal of possible impurities that may be influencing the performance of the catalysts studied.